In vivo study of paraspinal muscle weakness using botulinum toxin in one primate model. (March 2018) - Han, Sang Kuy; Lee, Youngjeon; Hong, Jung-Joo; Yeo, Hyeon-Gu; Seo, Jincheol; Jeon, Chang-Yeop; Jeong, Kang-Jin; Jin, Yeung Bae; Kang, Philyong; Lee, Sangil; Shin, Choongsoo S.; Kim, Young Eun; et al.
Abstract: Background: It has been generally speculated that paraspinal muscle weakness is related to the spinal degeneration including intervertebral disc failure. The purpose of this study was to investigate the effects of paraspinal muscle weakness induced by the botulinum toxin type-A on the lumbar spine and behavior pattern in an in-vivo primate model which has an upright locomotion similar to that of humans. Methods: Botox injections into paraspinal muscle of one cynomolgus monkey were conducted biweekly up to 19 weeks at L2–L3, L3–L4 and L4–L5. MRIs were performed for measurement of muscle cross-sectional areas and behavioral data were collected using a high-resolution portable digital video camera. Findings: The cross-sectional areas of the paraspinal muscles at L2–L3, L3–L4 and L4–L5 decreased by 8%, 12% and 8% at 21 weeks after the Botox injection, respectively. Intervertebral disc thickness at L2–L3, L3–L4 and L4–L5 decreased by 6%, 8% and 5% at 21 weeks after initial Botox injection, respectively. After the Botox injections, locomotion and movement activity of the monkey was decreased. The duration of sitting increased from 21% to a maximum of 97% at 9 weeks after the Botox injection, while stance time decreased from 9% to a minimum of 1% at 11 weeks post Botox injection. Interpretation: The findings of this study revealed that paraspinal muscle atrophy affects intervertebral disc morphology and locomotion activity of a primate and may lead to an onset of intervertebral disc degeneration. Highlights: Botox injection produces paraspinal muscle atrophy in this primate model. Paraspinal muscle atrophy affects a loss of intervertebral disc thickness. Paraspinal muscle atrophy affects a locomotion activity of a primate. Locomotion activity was more static post compared to pre-Botox injections.